2010
DOI: 10.1021/tx1003613
|View full text |Cite
|
Sign up to set email alerts
|

Base Flipping Free Energy Profiles for Damaged and Undamaged DNA

Abstract: Lesion-induced thermodynamic destabilization is believed to facilitate β-hairpin intrusion by the human XPC/hHR23B nucleotide excision repair (NER) recognition factor, accompanied by partner-base flipping, as suggested by the crystal structure of the yeast orthologue (Min, J. H., and Pavletich, N. P. (2007) Nature 449, 570–575). To investigate this proposed mechanism, we employed umbrella sampling to compute partner base flipping free energies for the repair susceptible 14R (+)-trans-anti-DB[a,l]P-N2-dG modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 17 publications
3
44
0
Order By: Relevance
“…Furthermore, UvrB is believed to interact with the damaged substrate through base stacking with a tyrosine residue at the base of the beta-hairpin and through a base flipping event [25], and the yeast homologue of human XPC-RAD23B [23] also utilizes base-flipping interactions with the protein. Base flipping free energy profiles and repair susceptibility of damaged DNA are currently under investigation [71]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, UvrB is believed to interact with the damaged substrate through base stacking with a tyrosine residue at the base of the beta-hairpin and through a base flipping event [25], and the yeast homologue of human XPC-RAD23B [23] also utilizes base-flipping interactions with the protein. Base flipping free energy profiles and repair susceptibility of damaged DNA are currently under investigation [71]. …”
Section: Discussionmentioning
confidence: 99%
“…The opening times for more stable, undamaged/matched DNA are expected to be much longer than for mismatch DNA (55). Although the 1D diffusion constants of Rad4/XPC on DNA are yet to be reported, studies have revealed microsecond-regime residence times per DNA site for a wide range of DNA-binding proteins (7)(8)(9)(10)(11)(12)(13).…”
Section: Significancementioning
confidence: 99%
“…Such differences result in different protein/DNA recognition and repair activities (see 3.4). Thermal destabilization was also observed using 14R(+)-transanti-DB [a,l]P-N 2 -dG adduct (Zheng et al, 2010) or 14S(-)-trans-anti-DB [a,l]P-N 6 -dA adducts whereas 14R(+) isomer stabilizes the ds-DNA (Cai et al, 2011). The hormone-derived genotoxic compound, 4-OHEN, derives from equilin and equilenin, two equine oestrogens present in hormone substitution therapies used to prevent the uncomfortable effects of menopauses but are also thought to increase breast cancer incidence in the population of hormonally-treated women (Rossouw et al, 2002).…”
Section: Carcinogens As Dna Destabilizing Agentsmentioning
confidence: 91%
“…This results in a base-flipping where the (+)-anti-B[a]P-N 2 -dG bulky adduct is located in the minor groove and the opposite cytosine is positioned in the major groove (Cosman et al, 1993). The precise orientation of this highly carcinogenic 10S(+)-trans-anti-B[a]P-N 2 -dG adduct depends on the sequence surrounding the target guanine (Cai et al, 2010). DNA is untwisted at 5'-CGG*C sites where a large bend is induced in the DNA helix, but not at 5'-CG*GC sequences where, conversely, DNA helix is destabilized in its portion orientated 5' to the lesion (Rodríguez et al, 2007).…”
Section: Carcinogens As Dna Destabilizing Agentsmentioning
confidence: 99%